2013
DOI: 10.3390/ijerph10116044
|View full text |Cite
|
Sign up to set email alerts
|

Lithium in Tap Water and Suicide Mortality in Japan

Abstract: Lithium has been used as a mood-stabilizing drug in people with mood disorders. Previous studies have shown that natural levels of lithium in drinking water may protect against suicide. This study evaluated the association between lithium levels in tap water and the suicide standardized mortality ratio (SMR) in 40 municipalities of Aomori prefecture, which has the highest levels of suicide mortality rate in Japan. Lithium levels in the tap water supplies of each municipality were measured using inductively cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 10 publications
3
51
0
1
Order By: Relevance
“…Die Resultate stimmen mit zuletzt zunehmenden ökologischen Studien aus Texas [4,5], Japan [6,30], Österreich [7] und Griechenland [8] überein, die nachweisen konnten, dass Lithiumvorkommen in der Umwelt -speziell im Trinkwasser -mit einer niedrigeren Suizidmortalität assoziiert sind.…”
Section: Diskussionunclassified
“…Die Resultate stimmen mit zuletzt zunehmenden ökologischen Studien aus Texas [4,5], Japan [6,30], Österreich [7] und Griechenland [8] überein, die nachweisen konnten, dass Lithiumvorkommen in der Umwelt -speziell im Trinkwasser -mit einer niedrigeren Suizidmortalität assoziiert sind.…”
Section: Diskussionunclassified
“…There is increasing evidence that Li is effective in lowering the risk of suicide [1]. Several meta-analyses have shown the antisuicidal effects of Li in people have depression and bipolar disorder [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Several epidemiological studies have shown the inverse association of lithium levels in tap water and suicide rates [1][2][3][4][5][6], although a few studies failed to find such association [7] or have reported an ambiguous association [8]. However, many people drink both mineral water and tap water.…”
Section: Introductionmentioning
confidence: 99%